Production Function Modeling of the Relationship between Quantity of Graduates and Federal Government Grants Case Studies: Universiti Sains Malaysia - R. Gobithasan; Anton Abdulbasah Kamil (Program Studi Statistika Unisba, 2006)
In recent years, much work has been constructed in the area of productivity and growth in order toidentify the link between factor inputs and output based on production function. However, in the fieldof tertiary education, there are less research to classify and discover a model to estimate theproduction of graduates in accord with the factor inputs. This paper discusses the usage ofproduction function in which the properties are specified in order to fit the tertiary education sectorwith reference to the data of Universiti Sains Malaysia (USM). It is then estimated with the Cobb-Douglas Production function (C-D). Aspects such as the inferences caused by multicollinearity,heteroscedasticity, and autocorrelation are also analyzed. In this approach, OLS and GLS type ofregression analysis have been carried out in order to analyze the productivity and growth of USM inproducing graduates. A suitable model produced by using two independent variables namelyemolument (from federal government operating expenditure) and capital (remaining federalgovernment grant plus federal government developing grant), is in fact presentable in the form of C-Dproduction function. The outcome of this study indicated a value greater than 1 for β1 and less than0 for β2 which implies that USM is experiencing an increasing marginal product of emolument, E andnegative marginal product of capital plus development grant, C.